Compressive behavior of bolted built-up steel columns fabricated using angle section columns. (December 2021) - Mou, Ben; Zhou, Yang; Qiao, Qiyun; Liu, Jiming
Abstract: High-strength steel columns are commonly connected by welding. However, the construction environment and quality of construction workers have a large impact on welding quality, especially on a construction site. This paper investigates the mechanical behavior of bolted built-up steel column, which is built using bolts instead of welds. Six bolted built-up steel columns were made using high-strength steel, referred as to H-SA700, and tested under axial loading to investigate the bearing capacity and buckling deformation. The main experimental parameter was the slenderness ratio. In addition, finite element models were established on the same scale as the tested specimens, and a supplementary parametric analysis on the effects of intervening plate thickness, intervening plate width, angle section side length, and bolt pitch on the bearing capacity of specimens was conducted. Moreover, the experimental and numerical results were compared with the calculated ultimate strength obtained from the corresponding codes of GB 50017–2017, ANSI/AISC 360–10, EN 1993-1-1, and AIJ-2002. The results showed that both slenderness ratio and angle section side length were the main factors on the bearing capacity. Japanese code gave the best predictions for the ultimate load of bolted built-up steel columns. Highlights: Six bolted built-up steel columns were under axial loading. Slenderness ratio and corner steel side length were the main factors. Japanese code gave the best predictions for the ultimate load.